Region‐Urbanicity Differences in Locus of Control: Social Disadvantage, Structure, or Cultural Exceptionalism?1. Issue 4 (4th June 2014) - Shifrer, Dara; Sutton, April
<x xml:space="preserve">Abstract</x> People with internal rather than external locus of control experience better outcomes in multiple domains. Previous studies on spatial differences in control within America only focused on the South, relied on aggregate level data or historical evidence, or did not account for other confounding regional distinctions (such as variation in urbanicity). Using data from the National Education Longitudinal Study, we find differences in adolescents' loci of control depending on their region and urbanicity are largely attributable to differences in their social background, and only minimally to structural differences (i.e., differences in the qualities of adolescents' schools). Differences that persist net of differences across adolescents and their schools suggest the less internal control of rural Southern adolescents, and the more internal control of rural and urban Northeastern adolescents, may be due to cultural distinctions in those areas. Results indicate region is more closely associated than urbanicity with differences in locus of control, with Western and Northeastern cultures seemingly fostering more internal control than Midwestern and Southern cultures. These findings contribute to research on spatial variation in a variety of psychological traits.